2015
DOI: 10.1007/s00253-015-7051-x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activities of three different Lactobacillus species and their production of antifungal carboxylic acids in wheat sourdough

Abstract: This study was undertaken to assess the antifungal performance of three different Lactobacillus species.Experiments were conducted in vitro and in situ to extend the shelf life of wheat bread. Standard sourdough analyses were performed characterising acidity and carbohydrate levels. Overall, the strains showed good inhibition in vitro against the indicator mould Fusarium culmorum TMW4.2043. Sourdough bread fermented with Lactobacillus amylovorus DSM19280 performed best in the in situ shelf life experiment. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 37 publications
6
80
0
Order By: Relevance
“…These organic acids have been highlighted in previous studies as antifungal compounds produced by LAB and therefore could be of interest to extend bakery product shelf-life (Axel et al, 2016a, b). Dal Bello et al (2007), Lavermicocca et al (2000) and Magnusson et al (2003) reported the production of phenyllactic acid in antifungal lactobacilli isolated from different sources.…”
Section: Quantitative Analysis Of Antifungal Molecules In Supernatantsmentioning
confidence: 90%
“…These organic acids have been highlighted in previous studies as antifungal compounds produced by LAB and therefore could be of interest to extend bakery product shelf-life (Axel et al, 2016a, b). Dal Bello et al (2007), Lavermicocca et al (2000) and Magnusson et al (2003) reported the production of phenyllactic acid in antifungal lactobacilli isolated from different sources.…”
Section: Quantitative Analysis Of Antifungal Molecules In Supernatantsmentioning
confidence: 90%
“…The analysis was carried out using a Waters Quattro premier XE UPLC system as described by Axel et al . (). The LC‐MS/MS method was operated in negative electrospray ionization mode to detect the antifungal compounds.…”
Section: Methodsmentioning
confidence: 97%
“…The use of natural preservatives would enable bakeries to market the so called "clean label" or "label friendly" products [40]. Thus, the "free-from" trend leads the bakery industry to reconsider traditional preservation methods and replace chemical preservatives with natural alternatives to guarantee a clean label [41].…”
Section: 'Clean Label' In Bakers Productsmentioning
confidence: 99%
“…reuteri R29 produced the highest total concentration of these active compounds in the sourdough, its addition to bread did not result in a longest shelf life. However, the chemical application of the antifungal carboxylic acids succeeded in a longer shelf life than achieved only by acidifying the dough (+25 %), which is an evidence of their contribution to the antifungal activity and their synergy [51].…”
Section: Biscuitsmentioning
confidence: 99%
See 1 more Smart Citation